The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/microorganisms7010022
|View full text |Cite
|
Sign up to set email alerts
|

Identification, Characterization, and Formulation of a Novel Carbapenemase Intended to Prevent Antibiotic-Mediated Gut Dysbiosis

Abstract: Antibiotics can damage the gut microbiome leading to opportunistic infections and the emergence of antibiotic resistance. Microbiome protection via antibiotic inactivation in the gastrointestinal (GI) tract represents a strategy to limit antibiotic exposure of the colonic microbiota. Proof of concept for this approach was achieved with an orally-administered beta-lactamase enzyme, SYN-004 (ribaxamase), that was demonstrated to degrade ceftriaxone excreted into the GI tract and protect the gut microbiome from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…SYN-006 is the oral formulation of P2A (targeted recombinant beta-lactamase 2), a Class B1 metallo-beta-lactamase isolated from B. cereus (Stiefel et al, 2005). P2A was manufactured in E. coli and formulated for oral delivery by incorporation into Eudragit ® -coated sucrose pellets designed for release of active enzyme at pH 5.5 or greater (Connelly et al, 2019). Formulation of P2A was similar to that of ribaxamase (Bristol et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…SYN-006 is the oral formulation of P2A (targeted recombinant beta-lactamase 2), a Class B1 metallo-beta-lactamase isolated from B. cereus (Stiefel et al, 2005). P2A was manufactured in E. coli and formulated for oral delivery by incorporation into Eudragit ® -coated sucrose pellets designed for release of active enzyme at pH 5.5 or greater (Connelly et al, 2019). Formulation of P2A was similar to that of ribaxamase (Bristol et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…To expand microbiome protection to all classes of beta-lactams, a novel metallo-beta-lactamase, P2A, isolated from Bacillus cereus (previously named targeted recombinant beta-lactamase 2) (Stiefel et al, 2005), was characterized. P2A demonstrated inactivation of a broad spectrum of beta-lactams including penicillins, cephalosporins, carbapenems, as well as antibiotic/beta-lactamase inhibitor combinations in vitro (Stiefel et al, 2005; Connelly et al, 2019). Further in vitro characterization revealed that P2A lost function at low pH (≤5.5), while retaining biological activity in the presence of human intestinal fluid, a key requirement for an enzyme intended for function in the GI tract (Connelly et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations